ATM antagonizes NHEJ proteins assembly and DNA-ends synapsis at single-ended DNA double strand breaks. Issue 17 (5th September 2020) - Britton, Sébastien; Chanut, Pauline; Delteil, Christine; Barboule, Nadia; Frit, Philippe; Calsou, Patrick
Abstract: Two DNA repair pathways operate at DNA double strand breaks (DSBs): non-homologous end-joining (NHEJ), that requires two adjacent DNA ends for ligation, and homologous recombination (HR), that resects one DNA strand for invasion of a homologous duplex. Faithful repair of replicative single-ended DSBs (seDSBs) is mediated by HR, due to the lack of a second DNA end for end-joining. ATM stimulates resection at such breaks through multiple mechanisms including CtIP phosphorylation, which also promotes removal of the DNA-ends sensor and NHEJ protein Ku. Here, using a new method for imaging the recruitment of the Ku partner DNA-PKcs at DSBs, we uncover an unanticipated role of ATM in removing DNA-PKcs from seDSBs in human cells. Phosphorylation of DNA-PKcs on the ABCDE cluster is necessary not only for DNA-PKcs clearance but also for the subsequent MRE11/CtIP-dependent release of Ku from these breaks. We propose that at seDSBs, ATM activity is necessary for the release of both Ku and DNA-PKcs components of the NHEJ apparatus, and thereby prevents subsequent aberrant interactions between seDSBs accompanied by DNA-PKcs autophosphorylation and detrimental commitment to Lig4-dependent end-joining.